Entrepreneurship Learning Model Based on Local Wisdom for Increasing Student Creative Business - Aryani, Rita (Indonesian Journal of Contemporary Education, 2019)
Creativity is the most important thing to make ends meet. With creativity will create a variety of innovations that are useful both fort themselves and others. Today local wisdom is a dynamic source of knowledge. Entrepreneurship based on local wisdom in improving student business can be a development for entrepreneur learning models at the College of Education and Teacher Training (STKIP). This study aims to identify the values of local wisdom and the creative endeavors of students to find entrepreneurship learning models on campus. This research uses depth-interview method and non-participation observation. To obtain the validity of the data triangulation was carried out with three creative business entrepreneur of student who were informant in this study. The results of this study are the reconstruction of entrepreneurial learning models based on local wisdom. In addition, intrapreneurship and entrepreneurship managerial behavior influenced by environmental factors. This research is useful for creating entrepreneurship learning models among student and can be used as a guide in entrepreneurship development.